Comparison of Flash Temperature at Cam–Tappet Interface Using Different Theoretical Models and Its Effect on Friction Torque. Issue 3 (3rd May 2020) - Umar, Muhammad; Mufti, Riaz A.; Khurram, Muhammad
Abstract: In this study, a numerical investigation is presented to calculate the flash temperature at the cam–tappet junction area using different easy-to-use theoretical models available in the literature. Flash temperature models use many assumptions and simplifications. Consequently, it will be beneficial to compare flash temperatures obtained from different models. It has been observed that the results obtained from different models vary substantially. Detailed reasoning has been provided for the variation in results. It has been found that high flash temperature is present in direct acting valve trains. The flash temperature caused the total friction force to decline. In light of experimental evidence, it can be deduced that the mixed friction force model shows less sensitivity to temperature.